338 PREVALENCE AND RISK FACTORS FOR LATENT TUBERCULOSIS INFECTION AMONG HEALTH CARE WORKERS IN THE COUNTRY OF GEORGIA. Issue 1 (1st January 2007) - Kempker, R.; Mirtskulava, V.; Shields, K.; Salakia, A.; Del Rio, C.; Leonard, M.; Blumberg, H. M.
Abstract : Purpose/Objectives: To estimate the prevalence and risk factors for latent tuberculosis infection (LTBI) among health care workers (HCWs) using the tuberculin skin test (TST) and the QuantiFERON-TB gold in tube test (QFT-G); to assess the frequency and factors associated with concordance and discordance between the two diagnostic tests. High rates of TB have been reported from Georgia and limited infection control measures have been implemented. Methods: A cross-sectional study was carried out among Georgian HCWs at the National TB Program (NTP) (inpatient TB hospitals and outpatient clinics) between June and August 2006. After providing written informed consent, HCWs completed a 3-page questionnaire, had 3 mL of blood drawn for the QFT-G test, and had a TST read 48 to 72 hours after placement. Results: 265 HCWs were enrolled into the study; the mean age was 42 years. Most were women (225, 86%), which reflects the gender distribution of HCWs at the NTP. Overall, 203 (77%) had a positive test result for at least one of the LTBI diagnostic tests, 177 (67%) had a positive TST, and 159 (60%) had a positive QFT-G. One hundred thirty-three (50%) were positive for both tests, 62 (23%) were negative for both tests, 44 (17%) had a positive TST but a negative QFT-G, and 26 (10%) had a positive QFT-G and a negative TST. There was moderately good agreement between the two tests (74%, kappa 0.4337 95% CI 0.326-0.5447). In multivariate analysis, employment of ≥ 5 years was significantly associated with an increased risk of a positive TST (OR = 6.96 [95% CI 3.91-12.40]) and QFT-G (3.62 [95% CI 2.10-6.24]). Conclusions: High rates of LTBI were noted among HCWs at the Georgian National TB Program, where few TB infection control measures have been available. The risk of having a positive diagnostic test for LTBI increased with length of employment. In the setting of frequent exposure to TB, there was moderately good agreement between the TST and QFT-G. These data also provide important baseline information as TB infection control measures are implemented.